Cultural and Political Perspective on Beethoven's "Ode to Joy" as the European Union's Anthem - Minaroy, Teodore Ignatius; Nugrahani, Henny Saptatia Drajati (Journal of Strategic and Global Studies, 2024)
ABSTRACT. The aim of this research is to explore the cultural and political significance of the Ode to Joy, a tune included in Beethoven's Ninth Symphony, so that tune can become an anthem for the European Union. Following the MEPs from Nigel Farage's Brexit party turning their backs on the playing of the European anthem, a discussion on this subject started. The method used in this research is descriptive qualitative approach and literature review. The research's conclusions demonstrate that both musically and politically, Ode to Joy has its significance. Ode to Joy had already come to represent Germany in Europe before it was officially adopted as the anthem of the European Union.